BIODEGRADASI PETROLEUM OLEH BAKTERI DARI SEDIMEN SUNGAI TALLO MAKASSAR - Idris, Agus Darmawan (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2014)
The purpose of this riset is to detect biodegradation capacity by bacteria from sediment river tallo makassar towards pollution from spilled oil around the river stream, this riset uses method sterilely sampling  in 3 different points stasion around tallo river stream. From prakultur stage and stage culture. in observation is got 2 different isolat from sample stasion 1 and 1 isolat from sample  stasion 2 with different 2 isolat from sample stasion 3, all morphology of this bacteria is a stick type and belong gram negative. Analysis towards biodegradation capacity of bacteria is by visual observation during incubation period with existence of  emulsifikasi phenomenon and colour change. in quantitative test of biodegradation capacity from each stasion, known the biggest biodegradation capacity happen in sample from stasion 2 that is 46,16 % and furthermore sample from stasion 1 that is 40,5 % with stasion 3 that is 22,05 %. in qualitative test uses kromatografi gas, based on result kromatogram relative perfect carbon chain severance happen in sample from stasion 2 that can degradation carbon chain c13 until c24 and in sample from stasion 1 carbon degradation process happens in carbon c13, c19, c22, c23, c27 while in sample from stason 3 degradation process happens in carbon c16, c18, c22,  and c24